Green Crime dalam Perspektif Hukum Pidana Islam: Analisis terhadap Kejahatan Lingkungan - Muzakkir, Muzakkir (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
This research is motivated by the increasing environmental degradation as a systemic crime and the weak enforcement of environmental law in Indonesia, which remains legal-formal without ethical and moral approaches. The aim of this study is to construct green crime as a delict in Islamic criminal law and to assess its relevance to national environmental law. This research employs a library research method with a normative-conceptual approach, analyzing data from the Qur'an, hadith, fiqh jinayah, maqāṣid al-shariah, and modern criminology literature. The main findings indicate that green crime can be constructed through the expansion of the meaning of fasād fi al-arḍ and the reinterpretation of the elements of jarīmah (actus reus and mens rea) to include systemic ecological damage. This concept is reinforced by maqāṣid al-shariah, particularly the protection of life, property, lineage, and the environment (ḥifẓ al-bi'ah). This research contributes to expanding contemporary fiqh jinayah and offers the integration of Islamic values into Indonesian environmental legal policies toward greater ecological justice.